Teaching world literature - Damrosch, David (New York : Modern Language Association of America, 2009)
This is an exciting, and unsettling, time to be teaching world literature, writes David Damrosch. Because the range of works taught in world literature courses has expanded enormously, both historically and geographically, the task of selection--and of teacher preparation--has grown more challenging. Teachers of this field must grapple with such issues as coverage, cultural difference, and the role of translation in the classroom. Should one emphasize masterpieces or traditions, concepts or themes? How does one avoid making a work bear the burden of representing an entire tradition? To what extent should anthologies be used? Can a course be global in scope and yet focus on a few works, authors, moments? This collection of thirty-two essays in the MLA series Options for Teaching offers an array of solutions to these challenges, reflecting the wide variety of institutions, courses, and students described by the contributors. An annotated bibliography is provided, with a listing of useful Web sites.
Courses. Introduction ; The adventures of the artist in world literature: a one-semester thematic approach / Carolyn Ayers ; American literature and Islamic time / Wai Chee Dimock ; Worlds of difference? Gay and Lesbian texts across cultures / Nikolai Endres ; Middle Eastern literature: an introduction / Carol Fadda-Conrey ; Cosmos versus empire: teaching the Ramayana in a comparative context / Raymond-Jean Frontain ; Off to join the online circus: the comic heroic journey of world literature / Elizabeth Horan ; Imagining the constructed body: from statues to cyborgs / Ellen Peel ; "Literature that changed the world": designing a world literature course / C.A. Prettiman ; Teaching world masterpieces through religious themes in literature / Eric Sterling ; Ancient and contemporary texts: teaching an introductory course in non-western literatures / Kathryn A. Walterschied.
Includes bibliographical references (pages 403-416) and index.
Keywords: Literature -- Study and teaching; Literature -- Study and teaching; Wereldliteratuur; Onderwijs; Literaturunterricht; Weltliteratur; Vergleichende Literaturwissenschaft; Aufsatzsammlung